2023
DOI: 10.1007/s00701-022-05456-8
|View full text |Cite
|
Sign up to set email alerts
|

Remission, complications, and overall survival in transsphenoidal pituitary surgery—a Swedish single-center experience of 578 patients

Abstract: Background Surgical treatment of pituitary lesions causing hormonal overproduction or mass effect is standard procedure. There are few reports on the results and complications related to these surgeries from Northern Europe. Our aim was to evaluate the outcome and complications of a single tertiary surgical center over more than a decade. Methods This was a retrospective study on all patients that underwent pituitary surgery from 1st of January 2005 to 31s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The second most common complication was rhinorrhea in 51 patients (8.4%). Meningitis (4%) and sepsis (2%) were identified as other common complications [ 10 ]. In the study conducted by Chowdhury et al with 149 patients, the most common complication was rhinorrhea (40%), followed by diabetes insipidus at 14.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common complication was rhinorrhea in 51 patients (8.4%). Meningitis (4%) and sepsis (2%) were identified as other common complications [ 10 ]. In the study conducted by Chowdhury et al with 149 patients, the most common complication was rhinorrhea (40%), followed by diabetes insipidus at 14.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that post-operative follow-up by an endocrinologist reduced the risk of 30-day readmission after surgery [ 38 , 39 ]. Cerebrospinal fluid leakage rates after transsphenoidal surgery have decreased since the introduction of a multidisciplinary surgical skull base team in a high-volume Swedish centre [ 40 ]. Pituitary MDT benefits have also been highlighted in a series of four women with sellar lesions during pregnancy [ 41 ].…”
Section: Benefits Of the Pituitary Mdt/ptcoementioning
confidence: 99%
“…In 29 of 60 (48.4%) German neurosurgical centres, otorhinolaryngologists are never involved in pituitary surgeries, whereas in only 8 centres (13.3%) surgeries are always performed together with an otorhinolaryngologist [ 91 ]. Nevertheless, the collaboration between pituitary neurosurgeons and otorhinolaryngologists during endonasal and other skull base surgical approaches is of extreme value, allowing higher tumour resection rates and fewer post-operative complications, particularly cerebrospinal fluid leakages [ 39 , 40 , 92 , 93 ].…”
Section: Characteristics Composition and Requirements Of The Pituitar...mentioning
confidence: 99%
See 1 more Smart Citation